2015
DOI: 10.1152/ajplung.00105.2015
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet is associated with impaired fetal lung development

Abstract: Maternal nutrition has a profound long-term impact on infant health. Poor maternal nutrition influences placental development and fetal growth, resulting in low birth weight, which is strongly associated with the risk of developing chronic diseases, including heart disease, hypertension, asthma, and type 2 diabetes, later in life. Few studies have delineated the mechanisms by which maternal nutrition affects fetal lung development. Here, we report that maternal exposure to a diet high in fat (HFD) causes place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 43 publications
(52 reference statements)
6
50
1
1
Order By: Relevance
“…In those pilot experiments we noted abnormal baseline Rrs and alveolar development. A recent publication expands and details these types of findings (Mayor et al 2015).…”
Section: Discussionmentioning
confidence: 89%
“…In those pilot experiments we noted abnormal baseline Rrs and alveolar development. A recent publication expands and details these types of findings (Mayor et al 2015).…”
Section: Discussionmentioning
confidence: 89%
“…For example, a high-fat diet alters fetal lung development: rats born to mothers fed a high-fat diet during gestation have higher levels of cytokines such as tumor necrosis factor-a in their lungs, as well as increased airway resistance and decreased respiratory system compliance (31). Furthermore, mice born to mothers fed a high-fat diet have delayed fetal lung development and reduced expression of surfactant proteins (32). Consumption of a high-fat diet during gestation could contribute to the development of asthma in offspring.…”
Section: Asthma Caused By Obesitymentioning
confidence: 99%
“…Maternal obesity and/or maternal HF diet studies are usually focused on the consequences to the offspring. [46][47][48] These studies vary greatly in terms of the mothers' diet before pregnancy, the duration and the amount of fat in the diet. Similar to our study, Tamashiro et al 49 exposed rats to a 60% HF diet starting on day 2 of gestation, measured body weight on days 14-21, and found no significant weight gain.…”
Section: Diet Reproductive Status and Weightmentioning
confidence: 99%
“…Animal studies that model maternal obesity, rather than administering HF diets during gestation, usually feed the HF diet many weeks before mating. Pereira et al 51 started female rats on a 45% fat diet 4 weeks before mating and found that they gained significantly more weight during pregnancy than control females, while Mayer et al 46 had female mice on a 42% fat diet for over 3 months before mating, and found that the animals lost a significant amount of weight compared to standard fed females. Gohir et al 52 found no differences in weight gain after eight weeks of a 45% fat diet or during pregnancy.…”
Section: Diet Reproductive Status and Weightmentioning
confidence: 99%